TUMOR NECROSIS FACTOR-ALPHA A POTENTIAL THERAPEUTIC TARGET FOR PERIODONTITIS AND DIABETES MELLITUS - Angela Widjaja; Ahmad Syaify; Hendrawati (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Diabetes mellitus (DM) is a systemic disease that affects many human populations in the world. One of DM’s oral complications is periodontitis. The pro-inflammatory cytokine that plays a major role in the relationship between these two diseases is TNF-α. Review: Diabetes mellitus is a systemic disease characterized by high blood glucose levels (hyperglycemia) due to inadequate insulin secretion, insulin resistance or both. Metabolic disorders caused by hyperglycemia can cause endothelial dysfunction in blood vessels. Endothelial dysfunction that occurs due to hyperglycemia can trigger an inflammatory response that can increase the progression of periodontitis. Periodontitis is a chronic inflammatory response in periodontal tissue to pathological microorganisms in dental biofilm. The periodontitis process begins with gingival inflammatory response. The initial phase of gingival inflammation is characterized by redness and bleeding on probing. Worsening inflammation will cause loss of periodontal tissue attachment and alveolar bone resorption which can lead to tooth loss. The inflammatory process that occurs in periodontitis involves pro-inflammatory cytokines that can influence insulin resistance, such as Tumor necrosis factor-alpha (TNF-α). Tumor necrosis factor-alpha is also a cytokine that plays a major role in the pathogenesis of diabetes mellitus, so that periodontitis and diabetes mellitus are interrelated diseases Conclusion: The TNF-α cytokine is a potential therapy target for periodontitis and diabetes mellitus.